The Analysis of the Bank Interest Influence and Exchange Rate Towards Composite Stock Price Index in Indonesia Using Vector Error Correction Model Approach - Mukhlis, I; Simanjuntak, T H; Prasetyo, T (KnE Social Sciences, 2018)
This study aims to analyze the influence of bank interest and exchange rate towards composite stock price index in Indonesia under the period of January 2010-December 2016. The method applied is Vector Error Correction Model (VECM). The findings show that this method aces to show the pace of adjusting balance from the short period up to long period towards stock price index variable. The gap between bank interest level and the exchange rate has the low impact towards composite stock price index. For a longer period, the exchange rate would bring negative impact to composite stock price in Indonesia. Meanwhile, in a short period, it would not affect exchange rate and bank interest rate towards stock price index in Indonesia. Keywords: Stock Price, Exchange Rate, Vector Error Correction Model, Bank Interest Rate